Hard Times: The United States and Mexico in NAFTA’s “Renegotiation” Process - Menezes, Roberto Goulart; Mariano, Karina Lilia Pasquariello [UNESP]; Contrera, Flávio [UNESP] (Pontifícia Universidade Católica do Rio de Janeiro, Instituto de Relações Internacionais, 2022)
After a tense process of renegotiating the terms of the NAFTA (North American Free Trade Agreement), the governments of the United States, Mexico and Canada established a new regional agreement, the USMCA (United States, Mexico and Canada Agreement), whose purpose is to overcome problems that emerged since the NAFTA came into force in 1994. The ratification of this document by the national congresses of the referred countries has generated new tensions and instabilities in their political scenario, especially due to the existing structural asymmetries between them. This work aims to analyse the impact of that imbalance in the NAFTA renegotiation process, considering the behaviour of the United States in relation to its partners, especially Mexico.

Após um tenso processo de renegociação dos termos do NAFTA (Acordo de Livre Comércio Norte-Americano), os governos dos Estados Unidos, México e Canadá estabeleceram um novo acordo regional: o USMCA (Acordo Estados Unidos, México e Canadá), cujo objetivo é superar problemas criados desde a entrada em vigor do NAFTA em 1994. A ratificação deste documento pelos respectivos congressos nacionais gerou novas tensões e instabilidades no cenário político destes países, especialmente devido às assimetrias que existem entre eles. Este trabalho visa analisar o impacto deste desequilíbrio no processo de renegociação do NAFTA, considerando o comportamento dos Estados Unidos em relação a seus parceiros, especialmente o México.
Tempos difíceis: os Estados Unidos e o México na “renegociação” do NAFTA
Keywords: Canada; United States; Mexico; NAFTA; USMCA; Canadá; Estados Unidos; México; NAFTA; USMCA